LABOR OUTREACH PROGRAM FDA DECISION DAY (Tufts Archival Research Center, 2007)
Outline of the Labor Outreach Program. Divides plan into six steps based on who should be contacted and how. Mentions contacts in labor, congress, and the house of representatives. Contains plans for press releases, direct and indirect contact, and phone calls.